2006
DOI: 10.1158/0008-5472.can-06-0577
|View full text |Cite
|
Sign up to set email alerts
|

BiP/GRP78 Is an Intracellular Target for MDA-7/IL-24 Induction of Cancer-Specific Apoptosis

Abstract: Melanoma differentiation-associated gene-7/interleukin-24 (mda-7/IL-24) is a unique member of the IL-10 gene family that induces cancer-selective growth suppression and apoptosis in a wide spectrum of human cancers in cell culture and animal models. Additionally, recent clinical trials confirm safety and document significant clinical activity of mda-7/ IL-24 in patients with diverse solid cancers and melanomas. Despite intensive study the molecular basis of tumor-cell selectivity of mda-7/IL-24 is not well cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 34 publications
6
136
0
Order By: Relevance
“…These results support the notion that BiP/GRP78 is an intracellular target for MDA-7/IL-24 induction of cancer-specific apoptosis. 49 Collectively, our data indicate that the activation of PKR, p38 MAPK and induction of ER stress could be involved in ZD55-IL-24-induced leukemia apoptotic cell death.…”
Section: Discussionmentioning
confidence: 69%
“…These results support the notion that BiP/GRP78 is an intracellular target for MDA-7/IL-24 induction of cancer-specific apoptosis. 49 Collectively, our data indicate that the activation of PKR, p38 MAPK and induction of ER stress could be involved in ZD55-IL-24-induced leukemia apoptotic cell death.…”
Section: Discussionmentioning
confidence: 69%
“…We reported that Ad.mda-7 induces an UPR pathway (17,18,24). The robust expression of MDA-7/IL-24 protein and the subsequent killing effect suggest that similar to Ad.mda-7, MDA-7/IL-24 may induce an UPR pathway.…”
Section: Mda-7/il-24 Protein Stimulates the Upr Pathway And Generatesmentioning
confidence: 90%
“…The successful transition of Ad.mda-7 into the clinic in a phase I clinical trial reinforces the hypothesis that mda-7/IL-24 is safe and affords remarkable potential as a cancer gene therapeutic. Moreover, secreted MDA-7/IL-24 protein, generated from Ad.mda-7-infected cells, promotes antiangiogenic, immunostimulatory, radiosensitizing and ''bystander'' antitumor activities (6,11,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,20,23 After Ad.mda-7 infection, the MDA-7/IL-24 protein interacts with the endoplasmic reticulum (ER) chaperone protein BiP/GRP78 and initiates a cascade of "unfolded protein response (UPR)/ER-stress response" events in tumor cells resulting in the activation of p38 MAPK and induction of growth arrest and DNA damage inducible (GADD) genes that culminate in apoptosis. [32][33][34] Interestingly, although MDA-7/IL-24 is localized in the ER in both normal and cancer cells, the ER-stress response-induced apoptosis induction is observed only in cancer cells of diverse tissue origin, but not in their normal counterparts. Recent findings show that the level of BiP/GRP78 is higher in multiple cancer cells than in normal cells, which might make cancer cells more susceptible to ER stress by mda-7/IL-24.…”
Section: Diverse Molecular and Signal Transduction Pathways Involved mentioning
confidence: 99%